Infrared spectroscopic study on residual chitosan-based composite seed coating in kaolin - Huang Lanchun; Wu Qian; Huang Teng; Enwen Wang; Kong Desong; Wang Hai (Scientific Reports)
Abstract The decomposition of residual chitosan-based composite seed coating in kaolin under different temperatures and salinities is analyzed with a Fourier transform infrared spectroscopy (FT-IR). The degradation cycle is 28 days. The results show that a residue of the chitosan-based composite seed coating still exists in the kaolin on Day 7. From Day 7 to Day 14, the degradation rate of the chitosan-based composite seed coating is relatively slow. On Day 21, the chitosan-based composite seed coating is degraded entirely, and the degradation rate is quick during this period. However, the residue of this seed coating after degradation has a chemical action with the kaolin. On Day 28, the chitosan-based composite seed coating and residue aree wholly degraded in the kaolin. The chitosan-based composite seed coating can be completely degraded without residue. When the salinity of the kaolin is less than 1.0% under 0 –3̄0 ℃, its degradation rate and products will not be affected by temperature and salinity.